Study on Community Land Rights in Niassa Province, Mozambique - Åkesson, Gunilla; Calengo, André; Tanner, Christopher (Swedish International Development Cooperation Agency (SIDA), 2009)
This report is based on information collected within the context of the study concerning Community Land Rights in Niassa Province in Mozambique, with special attention paid to the programme implemented by the Malonda Foundation. This programme is supported and financed by the Swedish Government and aims to promote private investment in the province while seeking, during the course of the process, to ensure equitable and beneficial social impact as an explicit objective, in particular for the local population.
ISBN 978-91-85735-17-4
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; employment / emprego; governance / governação; land governance / gestão de terra; youth / juventude

Institutional Change and Community Based Natural Resource Management in Northern Mozambique - Anstey, Simon (University of Zimbabwe, 2009)
The objective of this study is to examine how the extensive institutional change of reforms to policy and legislation in Mozambique over the past decade has affected evolutions at the local level in the governance of natural resources. The particular focus of the research is an analysis of a community based natural resource management (CBNRM) initiative in North Sanga District of Niassa Province and a longitudinal study of its development between 1999 and 2007 based on my involvement as both field practioner and researcher. The research reveals institutional change in the governance of natural resources by communities in North Sanga as non-linear, non-equilibrium and scale interactive; as well as the agency in change being contingent on specific contexts (historical, social and environmental) and responsive to the beliefs of the actors involved. The importance of ‘crisis’ in promoting new cycles of adaptation for local governance is emphasised as is the significance of gaining formal ownership of the land by the community in acting as a key promoter of their agency in institutional and governance change.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude